OPTIMALISASI KINERJA LEMBAGA OMBUDSMAN DAERAH ISTIMEWA YOGYAKARTA DALAM PENYADARAN HAK MASYARAKAT ATAS PELAYANAN PUBLIK - Muhammad Arif Wicaksono (Universitas Khairun, 2022)
The Ombudsman Institution is an independent institution which functions to supervise the public service performance issues. The existence of this institution is considered important to increase the public service especially for the public service performance by the government or local government and its existence is guaranteed by law. Ombudsman in its progress reaches the provincial level and the Ombudsman Institution is gradually formed in regions, including in Yogyakarta Special Region. The institution’s primary function and role is doing public service supervision both by having public reports and having active role in doing special investigation. Among the supervision and secretarial and research and developmental administration tasks, socialization task is an important task in performing right awareness on public services.Associated with the mentioned factors, the researcher desires to investigate the Ombudsman Institution of Yogyakarta Special Region especially in the Ombudsman Institution of Yogyakarta Special Region performance in doing its primary duty and function, in the Ombudsman Institution of Yogyakarta Special Region performance optimization in the right awareness on public service and the factors influencing the Ombudsman Institution of Yogyakarta Special Region performance optimization itself.This research uses the qualitative research method. The data gathered including the primary and secondary data. The primary data covers interview and observation data, meanwhile secondary data covers literature data and documentation. The analysis unit of this research is the Ombudsman Institution of Yogyakarta Special Region with the interviewed research subjects such as the Head, Institution Representative, Socialization, Cooperation, and Networking Unit, and Socialization Executive Assistant.The finding of this research shows that the establishment of The Governor Regulation Number 69 Year 2014 about the Organization and Working Procedure of the Ombudsman Institution of Yogyakarta Special Region causes the incorporation of 2 institutions, The Regional Ombudsman Institution (LOD) and the Private Ombudsman Institution (LOS), to be a single institution called as the Ombudsman Institution of Yogyakarta Special Region and it was started in 2015. The Ombudsman Institution of Yogyakarta Special Region performance optimization has been seen in its achievements which are in accordance with the applicable regulations. The optimization of socialization task on public right awareness toward public service done by the Ombudsman Institution of Yogyakarta Special Region is considered good and optimum. It can be seen from the programs done in the socialization intensity, socialization quality, and socialization portion compared to other activities. The factors influencing the Ombudsman Institution of Yogyakarta Special Region performance in doing its duties covering the executive human resources factor, facilities and infrastructure and public participation.These research findings directly contribute toward the science development especially on the Ombudsman Institution of Yogyakarta Special Region performance optimization both from supervision task performance and the optimization of socialization task on public right awareness toward public service. Keywords: Ombudsman, Public Service, Performance, Socialization, Right Awareness.